PENGELOLAAN BANK SAMPAH MILIK DESA DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DESA GUNTUNG - Siti Sahara; Zuhrinal Nawawi; Siti Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The aim of this research is to study or understand waste management in increasing community income in Guntung village. To find out the results of waste management at the village waste bank. This research uses a qualitative approach method. The types of data used in this research are primary and secondary data. Data collection techniques through interviews, documentation. The informants in this research were the chairman of the waste bank and employees of the Guntung village waste bank. The data analysis techniques used in this research are data reduction, data presentation and drawing qualitative descriptive conclusions. The results of research on the Management of Village-Owned Waste Banks in Increasing Community Income use the 3R principle, namely: (reduce) reduce the purchase of goods that contain a lot of waste, (reuse) reuse objects that can still be used, (recycle) recycle used goods into a product that has economic value. Based on the results of the analysis, the role of the waste bank in Guntung village is oriented towards increasing community income and community awareness in managing processed waste that has economic value.